Balance, Capacity, and the Contingencies of Everyday Life: Narrative Etiologies of Health Among Women in Street-Based Sex Work. (March 2020) - Orchard, Treena; Murie, Angela; Salter, Katherine; Elash, Holli-Lynn; Bunch, Mary; Middleton, Cathy; Benoit, Cecilia
There is an abundance of health research with women in street-based sex work, but few studies examine what health means and how it is practiced by participants. We embrace these tasks by exploring how a convenience sample of sex workers ( n = 33) think about and enact health in their lives. Findings reveal pluralistic notions of health that include neoliberal, biomedical, and lay knowledge. Health is operationalized through clinic/hospital visits and self-care practices, which emerge as pragmatic behaviors and ways to resist or compensate for exclusionary treatment in health care systems. Participants also use symbols of biomedical authority to substantiate their lay interpretations of certain conditions, revealing complex forms of moral reasoning in their health etiologies. We conclude that doing health and constructing rich narratives about it are constituent elements of the women's everyday praxis and subjectivities in relation to the broader socioeconomic and political worlds of which they are a part.